Increase Nursing Satisfaction with Electronic Emergency And Disaster System (SPEED) - Nofita Dewi Kok Mesa; Titin Andri Wihastuti; Fajar Ari Nugroho; Yulian Wiji Utami; Suryanto Suryanto; Heri Kristianto; Muchamad Supriyadi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Medical records are infrequently documented in prehospital services. Considering the benefits of Electronic Medical Record (EMR) have a significant impact on nurse satisfaction, quality of care, and quality of clinical decisions, it is essential to develop technologies that could facilitate prehospital services. The objective of this study was to determine if the Emergency and Disaster Electronic System (SPEED) program increased the job satisfaction of prehospital nurses involved in the documentation of medical data. The study design uses True Experimental Design with a Crossed Over Design approach. The study sample consisted of 54 participants divided into two groups. Group A received the SPEED intervention, whereas Group B received the paper-based intervention (Period 1). After the second period (washout phase), group A received a paper-based intervention whereas group B received the SPEED intervention (3rd period). The Job Satisfaction Survey was utilized for this study. Researchers utilized the Paired sample T test and the Independent sample t-test statistical tests. After receiving a SPEED intervention, the group's mean difference was a rise in job satisfaction, as indicated by the results. This shows that SPEED application interventions are more helpful in enhancing nurses' job satisfaction with medical record documentation. Abstrak: Pendokumentasian rekam medis dalam layanan prehospital jarang dilakukan. Pada layanan emergensi dibutuhkan Electronic Medical Record (EMR) karena berdampak pada kepuasan perawat, kualitas perawatan dan kualitas keputusan klinis Oleh karenanya dibutuhkan pengembangan inovasi yang dapat memudahkan dalam layanan prehospital. Tujuan penelitian untuk mengetahui pengaruh aplikasi Sistem Penanganan Elektronik Emergency dan Disaster (SPEED terhadap peningkatan kepuasan kerja perawat prehospital dalam pendokumentasian rekam medis. Desain penelitian menggunakan True Eksperimental Design dengan pendekatan Crossed Over Design. Sampel penelitian berjumlah 54 responden yang dibagi menjadi dua grup kelompok. Kelompok A diberikan intervensi SPEED dan kelompok B diberikan intervensi paper based (Periode ke-1). Setelah periode ke-2 (masa washout) maka terjadi pertukaran posisi yaitu kelompok B diberikan intervensi SPEED dan kelompok A diberi intervensi paper based (periode ke-3). Instrumen yang digunakan yaitu Job Satisfaction Survey. Peneliti menggunakan uji statistik Paired sample T test dan Independent sampel t test. Hasil penelitian menunjukan bahwa kenaikan kepuasan kerja pada kelompok sesudah diberikan intervensi SPEED. Hal ini menunjukkan bahwa intervensi aplikasi SPEED lebih efektif meningkatkan kepuasan kerja perawat dalam pendokumentasian rekam medis.